A case study to identify and describe instructional strategies used in the eleventh grade language arts classroom to assist disadvantaged students in preparing for the state reading assessment - Tresner, Carey A. (Kansas State University, 2010)
This case study explored multiple teachers’ instructional strategies in several eleventh grade Language Arts classrooms in one successful Midwest school. A “successful” Midwest school was defined as having attained AYP at least three consecutive years. The study focused on the specific instructional strategies and activities used when preparing disadvantaged students for the state reading assessment. The strategies were implemented with disadvantaged students who were difficult to motivate, were slower learners, and were categorized in at least one subgroup. Interviews were conducted with the eleventh grade Language Arts teachers to determine (a) the strategies used when motivating and preparing disadvantaged students for state assessments, (b) the formative practice assessment data used, (c) the instructional changes made based on the formative practice assessment results, (d) the perceived impacts of the preparation process on student improvement, and (e) the recommendations of the eleventh grade Language Arts teachers in preparation for the state reading assessment. Furthermore, this case study explored the perspectives of administrative leaders on the preparation of eleventh grade Language Arts teachers preparing eleventh grade disadvantaged Language Arts students for the state reading assessment. Interviews were conducted with the administrative leaders to determine (a) the resources available in the school district to assist eleventh grade disadvantaged Language Arts students in preparation for the state reading assessment (b) the workshops and conferences that the school district allowed eleventh grade Language Arts teachers to attend in order to increase their understanding of different strategies, and (c) the recommendations of the administrative leaders in preparation for the state reading assessment. Data support that the components of the framework (recognition, memorization, conservation of constancy, classification, spatial orientation, temporal orientation, and metaphorical thinking) were implemented by all of the eleventh grade Language Arts teachers in a variety of ways. The eleventh grade Language Arts teachers also implemented research-based strategies in the classroom to strengthen the framework. The research-based strategies included: structured lessons, relevant curriculum, comprehensive instruction, collaborative learning, strategic tutoring, formative assessment, drill and practice, test-taking strategies, hands-on experience, special privileges, and extra time. Furthermore, the eleventh grade Language Arts teachers administered four formative practice assessments. With the results of these assessments, the eleventh grade Language Arts teachers determined what the eleventh grade disadvantaged Language Arts students understood and what the students did not understand. Based on the formative practice assessment results, the eleventh grade Language Arts teachers changed their strategies and focused on the components in which the eleventh grade disadvantaged Language Arts students were weak.
Keywords: Disadvantaged students; Instructional strategies; Research-based strategies; at-risk students; Language arts students; special education students; Education, Curriculum and Instruction (0727)